Geomagnetic activity dependence and dawn-dusk asymmetry of thermospheric winds from 9-year measurements with a Fabry–Perot interferometer in Tromsø, Norway - Oyama, S.-i. (Shin-ichiro); Aikio, A. (Anita); Sakanoi, T. (Takeshi); Hosokawa, K. (Keisuke); Vanhamäki, H. (Heikki); Cai, L. (Lei); Virtanen, I. (Ilkka); Pedersen, M. (Marcus); Shiokawa, K. (Kazuo); Shinbori, A. (Atsuki); Nishitani, N. (Nozomu); Ogawa, Y. (Yasunobu) (Springer Nature, 2023)
Abstract Ion drag associated with the ionospheric plasma convection plays an important role in the high-latitude thermospheric dynamics, yet changes in the thermospheric wind with geomagnetic activity are not fully understood. We performed a statistical analysis of the thermospheric wind measurements with a Fabry–Perot interferometer (FPI; 630 nm wavelength) in Tromsø, Norway, in the winter months for 9 years. The measurements were sorted by a SuperMAG (SME) index, and a quiet-time wind pattern was defined as an hourly mean under SME ≤ 40 nT. The quiet-time wind pattern can be expected to be represented by a pressure gradient associated with the solar radiation and a geostrophic force balance. With an increase in the geomagnetic activity level, the thermospheric wind turned over from eastward to westward at dusk and increased the equatorward magnitude from midnight to dawn. Deviations from the quiet-time wind presented similar patterns in the direction with the ionospheric plasma convection but were larger in magnitude at dusk than at dawn. This is the first study to report a dawn-dusk asymmetry of the thermospheric wind acceleration feature and signatures of the eastward wind acceleration at dawn by ion drag.